VARIASI PERSEPSI SISWA TERHADAP MAKNA HAKIKI DAN MAKNA KONTEKSTUAL KATA TOLERANSI DALAM KEHIDUPAN BERAGAMA - Main Sufanti; Aan Sofyan; Atiqa Sabardila; Fitri Puji Rahmawati (Jurnal Penelitian Humaniora, 2014)
The purpose of this study is to describe: (1) students’ perception of the essential meaning of the word tolerance on religious life and (2) students’ perception of  the contextual meaning of the word tolerance in religious life. The subjects were high school students Muhammmadiyah 1 and  2 Surakarta, total number of students,  97. Data were collected with an open questionnaire and interviews and analyzed with interactive analysis. The results showed that (1) threre were thirteen variations of students’ perception of the essential meaning of the word tolerance in religious life, (2) there were nine students’ perception of the contextual meaning of religious tolerance. Most of the thirteen perceptions were substantially similar to those of the KBBI (2007), however, having shorter and different wordings. The perception that semantically the same substance is dealing with respect other religions, while those with different wordings but semantically the same are not to insult, criticize, or make fun of other people of different religions, to know and understand other religious life, no discrimination to others, a sense of mutual need between one individual to another individual, tolerant of others, caring for others, respect other religions, maintaining good relations between people, not overbearing, giving opportunity to others, living in harmony, and mutual assistance in the community. The perception of the meaning of the word tolerance varies contextually as the following: having exactly the same wordings, having different wordings but semanti cally the same, and having different contextual meanings.